SLUMPING PROCESSES ON THE CAUCASIAN CONTINENTAL SLOPE OF THE BLACK SEA - Moskalenko V.N.; Artemenko V.I.; Esin N.V.; Murdmaa I.O.; Levchenko O.V.; Platonova E.V. (My University, 2006)
New results of geomorphological, seismoacoustic, and lithological investigations on the upper continental slope off the Arkhipo-Osipovka Settlement are presented. Here, a large submarine slump was discovered by seismic survey in 1998. The assumed slump body, up to 200 m thick, rises 50-60 m above the valley floor that cuts the slope. Recent semiliquid mud that overlies laminated slope sediments with possible slump deformations flows down in the valley thalweg. Radiocarbon age inversion recorded in a Holocene sediment section of shelf facies recovered from the upper slope points to the gravity dislocation of sediments. © Pleiades Publishing, Inc., 2006.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен